Factors influencing the oxygen consumption of the isolated uterus of rats and mice - Khayyal, Mohammed Amin (The University of Edinburgh, 1932)
Regular cyclic changes in the functional activity, histology and weight of the secondary female sexual organs are known to be dependent on the sex hormones.

Mammary cycles in the unmated female mammal have been described in the rat by Meyers (52), and Sutter (67), in the guinea pig by Loeb and Hisselberg (48), in the cow by Hammond (33), and in the human by Dieckmann (23).

Vaginal cyclic changes are known to occur in certain species of animals. Marshall (51) and Hammond and Marshall (34) described such changes in the ferret. Loeb (47), Stockard and Papanicolow (66) and Voss (68) studied these phenomena in the guinea -pig. Lataste (45), Long and Smith (50), Morau (54), Long and Evans (49), and Allen and Doisy (2) described them in the mouse and rat.

Uterine cyclic changes, however, occur in all classes of mammals. These changes are of a very profound character, and this fact suggested that the estimation of the oxygen consumption of the uterus would offer an indication of the mode of action of the endocrine secretions which brought about the changes. The investigations described below were carried out by the writer in order to study the effect of the sex hormones on the oxygen consumption of the isolated uterus. Mice and rats were chosen as experimental animals, because the vaginal smear technique of Long and Evans (49) and Allen and Doisy (2) offered a simple method of diagnosing the various stages of the oestrous cycle in these animals.

These investigations have been carried out in two parts: Part I - The Estimation of the Oxygen Consumption of the Isolated Uterus during the various Stages of Sexual Development, and also during the different Stages of the Oestrous Cycle, and Part II - The Estimation of the Oxygen Consumption of the Isolated Uterus in Animals to which the various Sex Hormones had been Administered.